New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part V. Genera Pseudolycoriella Menzel & Mohrig and Phytosciara Frey - Mohrig, Werner; Kauschke, Ellen (Zootaxa, 2019)
In the Nearctic region the genus Pseudolycoriella currently includes 13 species. The following seven species are new to science: Psl. basisetosa sp. n., Psl. brevialata sp. n., Psl. chlorothoracica sp. n., Psl. flavipila sp. n., Psl. longisetosa sp. n., Psl. nocturna sp. n. and Psl. subjucunda sp. n. All species are keyed, figured and distribution data is given. Ostroverkhovana Komarova, 2002 is regarded as a junior synonym of Pseudolycoriella Menzel & Mohrig, 1998. Phytosciara (Prosc.) plusiochaeta (Hippa & Vilkamaa, 1991) is reported from North America for the first time.